Changes in suspension properties of structural modified montmorillonites - Volzone,C. (2001)
Rheological changes were found in smectite (Wyoming- and Cheto-type montmorillonites) suspensions after structural modifications. The effect of the particle size and Na+ exchange on the flow curves of 6% wt/wt suspensions of smectites with and without Na2CO3 were examined. Mineralogical, structural and physicochemical characteristics were studied by X-ray diffraction (XRD), infrared spectroscopy (IR), cationic exchange capacity (CEC), Mg2+, Al3+ determinations, particle size distribution and swelling index (SI). Grinding in an oscillating mill modified the particle sizes. The montmorillonite grain size and the structural disorder increased after larger grinding times. The grinding treatment modified the apparent viscosity and the yield stress of the montmorillonite suspensions. The homoionic Na Cheto-type montmorillonite with fine particle size (obtained by grinding) increased the flow properties. Nevertheless, rheological properties were lower than those of suspensions of the Wyoming-type montmorillonite. Montmorillonite-types reacted differently with Na2CO3 additions and this behavior may be related to their structural composition. The Na2CO3 activation improved the flow properties of the original Wyoming-type montmorillonite and after 30 s grinding.